The wisdom and power of the cross the passion of Christ in theology and the arts - late modernity and postmodernity - Viladesau, Richard 1944- (Oxford University Press, 2020)
"This volume is the fifth in a series dealing with the passion and death of Christ - symbolized by "the cross" -- in Christian theology and the arts. It examines the way the passion of Christ has been thought about by theologians and portrayed by artists and musicians in the modern and contemporary world. It examines the traditional approaches to soteriology in contrast to revisionist theologies that take up the challenge of understanding the meaning of the cross in the light of critical historical studies and modern science"--